Falls in the elderly: Spectrum and prevention - Al-Aama, Tareef (College of Family Physicians of Canada, 2011)
OBJECTIVE: To provide family physicians with a practical, evidence-based approach to fall prevention in the elderly. SOURCES OF INFORMATION: MEDLINE was searched using terms relevant to falls among the elderly in the community and in institutions. Relevant English-language papers published from 1980 to July 2010 were reviewed. Relevant geriatric society guidelines were reviewed as well. MAIN MESSAGE: Falls are a common and serious health problem with devastating consequences. Several risk factors have been identified in the literature. Falls can be prevented through several evidence-based interventions, which can be either single or multicomponent interventions. Identifying at-risk patients is the most important part of management, as applying preventive measures in this vulnerable population can have a profound effect on public health. CONCLUSION: Family physicians have a pivotal role in screening older patients for risk of falls, and applying preventive strategies for patients at risk.